Direct Observation of Early‐Stage High‐Dose Radiotherapy‐Induced Vascular Injury via Basement Membrane‐Targeting Nanoparticles. Issue 48 (18th November 2015) - Au, Kin Man; Hyder, Sayed Nabeel; Wagner, Kyle; Shi, Caihong; Kim, Young Seok; Caster, Joseph M.; Tian, Xi; Min, Yuanzeng; Wang, Andrew Z.
Abstract : Collagen IV‐targeting peptide‐conjugated basement membrane‐targeting nanoparticles are successfully engineered to identify early‐stage blood vessel injury induced by high‐dose radiotherapy.